1062. Daptomycin/Ceftaroline in Combination vs. Vancomycin for the Treatment of Methicillin-Resistant Staphylococcus aureus Bacteremia. (26th November 2018) - Fox, Matthew; Zeqollari, Klarida; Lee, Grant; Pontiggia, Laura; Byrne, Dana; Adams, Jessica; King, Madeline; Rose, Lucia
Abstract: Background: Vancomycin has historically been the mainstay of therapy for MRSA bacteremia, but severe infections due to vancomycin-intermediate Staphylococcus aureus have emerged. In vitro studies have shown that the combination of a β-lactam antibiotic, such as ceftaroline with daptomycin, was synergistic against MRSA. The purpose of this study was to compare outcomes in patients who received daptomycin and ceftaroline in combination vs. vancomycin for the treatment of MRSA bacteremia. Methods: This was a retrospective exploratory cohort study approved by the institutional review board at Cooper University Hospital. Patients were included if they received daptomycin/ceftaroline (cases) or vancomycin (controls) for the treatment of MRSA bacteremia between November 2010 and March 2017. Cases were matched 1:1 with controls based on source of MRSA bacteremia, age within 10 years, and renal function. The primary endpoint was clinical cure, defined as the improvement of signs and symptoms of bacteremia. Secondary endpoints included microbiologic cure, time to sterilization of blood cultures, duration of hospital stay, overall mortality, and MRSA-related mortality. Results: Forty-one cases were included. There was no statistical difference between the two groups in microbiologic cure, time to sterilization of blood cultures, overall mortality, or MRSA-related mortality. There were no significant differences between patients in each group including in those with ICU admissions and who required vasopressors. Cases were significantly more likely to have hardware compared with the control group (43.9% vs. 12.2%; P = 0.0014). Clinical cure was achieved in 27 patients (65.9%) in the case group and 26 patients (63.4%) in the control group ( P = 0.8173). Patients in the case group had a statistically longer mean hospital duration (29 days vs. 21 days, respectively, P = 0.0206) and more secondary complications such as bone infection ( P = 0.0076). Conclusion: Time to sterilization of blood cultures and overall mortality were similar in both groups. Patients in the combination group had longer hospital stays compared with vancomycin monotherapy. Daptomycin/ceftaroline combination therapy is an option for complicated MRSA bacteremia. Larger studies should be conducted to further evaluate this combination. Disclosures: All authors: No reported disclosures.